Zadowolenie klienta wewnętrznego warunkiem sukcesu firmy usługowej - Korczak, Jerzy; Kijewska, Kinga (Internal Customer's Satisfaction as a Condition of Success of a Service Company, 2008)
The paper touches upon the problem of the identification of the satisfaction level of an internal customer. It presents the position of an internal customer within the TQM system, the influence of the communication processes in the relations between managers and internal customers on the increase in their commitment to their work, the effectiveness of tools for measuring the internal customers' satisfaction in the analyzed company. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 482-493